The Concept of Metaphor according to the philosophers C. S. Peirce and U. Eco – a tentative comparison - Sørensen, Bent (Signs - International Journal of Semiotics, 2011)
According to both Peirce and Eco metaphor can play an important role in the generation of sense and new knowledge. When Peirce defined metaphor as a hypoicon he was a scholastic realist. Before his “epistemic break” in the nineties Eco, on the other hand, was a nominalist - even though Eco was highly inspired by Peirce's ideas of signifying construction as an unlimited sign- exchanging process. This fundamental epistemological difference necessarily gives some evident differences in the perception of metaphor. Some of these differences will be presented in the following article.